Predicted Purchasing Decisions from Lifestyle, Product Quality and Price Through Purchase Motivation - Herawati, Herawati; Prajanti, Sucihatiningsih Dian Wisika; Kardoyo, Kardoyo (Journal of Economic Education, 2019)
Nowadays, Batik has become a fashion trend and lifestyle of the people. Certainly, It gives an impact on the growing need for so many emerging batik businesses in Indonesia. Lifestyle, product quality, price, and purchase motivation are factors that predicted influence and participate in determining consumers before making a purchasing decision. This study aimed to analyze and describe the influence of lifestyle, product quality, and price, either directly or indirectly, on purchasing decisions through purchase in the buying motivation at Trusmi Batik Cirebon Showroom. The research used the quantitative method with path analysis were processed using SPSS. The populations of this reaserch were all consumers who buy at Trusmi Batik Cirebon Showroom. The samples were 110 respondents, with accidental sampling method. The results showed (1) the influence of lifestyle on purchasing decisions directly and indirectly through the purchase of a greater motivation indirect influence. (2) The impact of product quality on purchase decisions directly and indirectly through the purchase of a greater motivation indirect influence. (3) The effect of price on purchase decisions directly and indirectly through the purchase of a greater motivation indirect influence. (4) Motivation to purchase gave a positive and significant influence on purchasing decisions in Trusmi Batik Cirebon Showroom. (5) Product quality is the most dominant variable in influencing purchasing decisions and purchase motivation is proven to be a good mediation between lifestyle variables, product quality and price of purchasing decisions.